The impact of venture capital on the persistence of innovation activities of Swiss start-ups - Spyros Arvanitis; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2013)
In this study we investigate the impact of early stage venture capital on innovation activities of Swiss start-ups. This is done based on a cohort of start-ups that is representative of all firms founded in Switzerland in 1996/97 as recorded by a census of the Swiss Federal Statistical Office for this period. We analyze not only the impact of early stage venture capital on innovation performance 3 years after firm foundation but also 6 and 9 years after firm start, respectively, for those firms that survived so long and reported continuously innovation activities (persistence of innovation). The results support neither the hypothesis of a positive impact on initial innovation activities nor the hypothesis of a positive time-persistent effect on innovation performance of start-ups.
Keywords: L20; O31; 330; venture capital; start-ups; innovation performance; Unternehmensgründung; Risikokapital; Innovation; Unternehmenswachstum; Schweiz